2019
DOI: 10.1155/2019/1629321
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Model and Algorithm for Multimodal Distribution of Emergency Supplies after Earthquake in the Perspective of Fairness

Abstract: After the earthquake, it is important to ensure the emergency supplies are provided in time. However, not only the timeliness, but also the fairness from different perspectives should be considered. Therefore, we use a multilevel location-routing problem (LPR) to study the fairness of distribution for emergency supplies after earthquake. By comprehensively considering the time window constraints, the partial road damage and dynamic recovery in emergency logistics network, the stochastic driving time of the veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Tzeng et al [3] considered the characteristics of emergency material allocation after the earthquake and studied the multi-objective location (LAP) model of emergency transit facilities. Xiong et al [4] aimed to maximize the satisfaction of transportation time and the fairness of material distribution, based on the two-level programming method. They studied the location-intermodal problem in the emergency logistics system after the earthquake, and designed a corresponding hybrid genetic algorithm.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Tzeng et al [3] considered the characteristics of emergency material allocation after the earthquake and studied the multi-objective location (LAP) model of emergency transit facilities. Xiong et al [4] aimed to maximize the satisfaction of transportation time and the fairness of material distribution, based on the two-level programming method. They studied the location-intermodal problem in the emergency logistics system after the earthquake, and designed a corresponding hybrid genetic algorithm.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…As shown in Table 6, the application of LRP models to optimize a case of waste management network planning (e.g., Rahim and Sepil, 2014;Sheriff et al 2014;Asefi et al, 2019;Hu et al, 2019) is by far the most popular study. Other popular application areas are emergency and disaster management (Rath and Gutjahr, 2014;Wang et al, 2014;Bozorgi-Amiri and Khorsi, 2016;Xu et al, 2016;Burkart et al, 2017;Veysmoradi et al, 2018;Wu et al, 2018;Liu et al, 2019a;Xiong et al, 2019), food distribution network planning (Solak et al, 2014;Hemmelmayr et al, 2017;Wu et al, 2017;Validi et al, 2018;Wang et al, 2018bWang et al, , 2018cChao et al, 2019;Saragih et al, 2019), and city logistics (Zhou et al, 2016; Zhou et al, 2017;Wang et al, 2018b;Chao et al, 2019;Rodriguez et al, 2019;Saragih et al, 2019;Schmidt et al, 2019). Each of these areas presents unique challenges for the researchers in the efforts to develop a model that correctly represents the real-life situation.…”
Section: Type Of Studymentioning
confidence: 99%
“…From the customers' perspective, Bozorgi-Amiri and Khorsi (2016) and Liu et al (2019a) considered minimizing the maximum demand shortage of a customer, in order to construct a fair allocation policy for relief distribution in a postearthquake, and for each demand point to receive a similar proportion of goods. Meanwhile, from the workers' perspective, it is observed that several works have attempted to balance the distance traveled by each vehicle (Martinez-Salazar et al, 2014;Golmohammadi et al, 2016;Rabbani et al, 2018a;Hadian et al, 2019;Basirati et al, 2019), the working time of each vehicle (Zhang et al, 2018;Liu et al, 2019a;Mara et al, 2019;Xiong et al, 2019), or the workload of each facility (Khalili-Damghani et al, 2015).…”
Section: Objective Functionmentioning
confidence: 99%
“…Du et al [35] consider fairness concerns for the supplier and the manufacturer with sustainable green technology innovation development and find that fairness concerns can promote and coordinate the supply chain members to invest more on their sustainable green technology. Various types of supply chains begin to take account of fairness such as cooperative advertising [36], private information [8,37], logistics service supply chain [38], and sustainable supply chain [39]. Chen et al [40] formulate the retailer's fairness-concerned utility function, and then develop a two-echelon supply chain model to study the combined impacts of fairness concerns and buyback guarantee financing on equilibrium strategies and supply chain performance.…”
Section: Literature Reviewmentioning
confidence: 99%